Removal of ZN (II) Metal Ions From Aqueous Solution By Aluminium Oxide (AL2 O3): A Kinetic And Equilibrium Study - Sen, Tushar; Mei, C. (Research Science Press (India), 2012)
In this work the adsorptive properties of aluminium oxide in the removal of zinc (Zn2+) from aqueous solution have been studied by laboratory batch adsorption kinetic and equilibrium experiments.The results show that the amount of adsorption of zinc metal ion increases with initial metal ion concentration, contact time, solution pH, temperature but decreases with the amount of adsorbent respectively. Overall the kinetic studies showed that the Zn (II) adsorption process followed pseudo-second-order kinetics and it is a two steps process: a very rapid adsorption of zinc metal ion to the external surface is followed by possible slow decreasing intraparticle diffusion in the interior of the adsorbent. Isotherm data reveals that the adsorption process follows both Freundlich and Langmuir isotherm. The value of separation factor, RL from Langmuir equation and rate of adsorption, ‘n’ from Freundlich model also gives an indication of favourable adsorption. Finally thermodynamic parameters are determined at three different temperatures and it has been found that the adsorption process is endothermic due to positive In this work the adsorptive properties of aluminium oxide in the removal of zinc (Zn2+) from aqueous solution have been studied by laboratory batch adsorption kinetic and equilibrium experiments.The results show that the amount of adsorption of zinc metal ion increases with initial metal ion concentration, contact time, solution pH, temperature but decreases with the amount of adsorbent respectively. Overall the kinetic studies showed that the Zn (II) adsorption process followed pseudo-second-order kinetics and it is a two steps process: a very rapid adsorption of zinc metal ion to the external surface is followed by possible slow decreasing intraparticle diffusion in the interior of the adsorbent. Isotherm data reveals that the adsorption process follows both Freundlich and Langmuir isotherm. The value of separation factor, RL from Langmuir equation and rate of adsorption, ‘n’ from Freundlich model also gives an indication of favourable adsorption. Finally thermodynamic parameters are determined at three different temperatures and it has been found that the adsorption process is endothermic due to positive delta H0 accompanied by decrease in Gibbs free energy change (ΔG0).In this work the adsorptive properties of aluminium oxide in the removal of zinc (Zn2+) from aqueous solution have been studied by laboratory batch adsorption kinetic and equilibrium experiments.The results show that the amount of adsorption of zinc metal ion increases with initial metal ion concentration, contact time, solution pH, temperature but decreases with the amount of adsorbent respectively. Overall the kinetic studies showed that the Zn (II) adsorption process followed pseudo-second-order kinetics and it is a two steps process: a very rapid adsorption of zinc metal ion to the external surface is followed by possible slow decreasing intraparticle diffusion in the interior of the adsorbent. Isotherm data reveals that the adsorption process follows both Freundlich and Langmuir isotherm. The value of separation factor, RL from Langmuir equation and rate of adsorption, ‘n’ from Freundlich model also gives an indication of favourable adsorption. Finally thermodynamic parameters are determined at three different temperatures and it has been found that the adsorption process is endothermic due to positive delta H0 accompanied by decrease in Gibbs free energy change (ΔG0).In this work the adsorptive properties of aluminium oxide in the removal of zinc (Zn2+) from aqueous solution have been studied by laboratory batch adsorption kinetic and equilibrium experiments.The results show that the amount of adsorption of zinc metal ion increases with initial metal ion concentration, contact time, solution pH, temperature but decreases with the amount of adsorbent respectively. Overall the kinetic studies showed that the Zn (II) adsorption process followed pseudo-second-order kinetics and it is a two steps process: a very rapid adsorption of zinc metal ion to the external surface is followed by possible slow decreasing intraparticle diffusion in the interior of the adsorbent. Isotherm data reveals that the adsorption process follows both Freundlich and Langmuir isotherm. The value of separation factor, RL from Langmuir equation and rate of adsorption, ‘n’ from Freundlich model also gives an indication of favourable adsorption. Finally thermodynamic parameters are determined at three different temperatures and it has been found that the adsorption process is endothermic due to positive ΔH0 accompanied by decrease in Gibbs free energy change (ΔG0).